2022
DOI: 10.1021/acs.biomac.2c00837
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Biomimetic Trogocytosis with Farnesylated Chemically Self-Assembled Nanorings

Abstract: Inspired by the natural intercellular material-transfer process of trans-endocytosis or trogocytosis, we proposed that targeted farnesylated chemically self-assembled nanorings (f-CSANs) could serve as a biomimetic trogocytosis vehicle for engineering directional cargo transfer between cells, thus allowing cell–cell interactions to be monitored and facilitating cell–cell communications. The membranes of sender cells were stably modified by hydrophobic insertion with the targeted f-CSANs, which were efficiently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 63 publications
(123 reference statements)
0
9
0
Order By: Relevance
“…The E1-DHFR 2 -MMAE CSANs were shown to be efficiently internalized by A431-R cells through specific EGFR binding, which was confirmed by the significantly higher fluorescent CSAN signal when the cells were treated at 37 °C compared with 4 °C. A significant reduction in fluorescent CSAN internalization was observed when the cells were incubated in the presence of unlabeled anti-EGFR CSANs, consistent with previous studies of anti-EGFR CSAN target specificity (Figure b). , Additionally, the surface binding and internalization of the E1-DHFR 2 -MMAE CSANs were also imaged by fluorescence microscopy. Those studies revealed that the CSANs underwent cellular uptake by the EGFR + A431-R cells, indicated by the green punctate spots from the CSANs within the cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The E1-DHFR 2 -MMAE CSANs were shown to be efficiently internalized by A431-R cells through specific EGFR binding, which was confirmed by the significantly higher fluorescent CSAN signal when the cells were treated at 37 °C compared with 4 °C. A significant reduction in fluorescent CSAN internalization was observed when the cells were incubated in the presence of unlabeled anti-EGFR CSANs, consistent with previous studies of anti-EGFR CSAN target specificity (Figure b). , Additionally, the surface binding and internalization of the E1-DHFR 2 -MMAE CSANs were also imaged by fluorescence microscopy. Those studies revealed that the CSANs underwent cellular uptake by the EGFR + A431-R cells, indicated by the green punctate spots from the CSANs within the cells.…”
Section: Resultsmentioning
confidence: 99%
“…An anti-EGFR Fn3 domain generated through yeast surface display and screening was genetically fused to the N-terminus of the DHFR 2 fusion protein to serve as the targeting ligand. ,, A C-terminal CVIA sequence incorporated into the DHFR 2 fusion proteins was also previously demonstrated to be efficiently recognized and prenylated with various farnesyl diphosphate derivatives. To afford bioconjugation, the E1-DHFR 2 -CVIA monomer was efficiently farnesylated with an azide-containing farnesyl analog (C10-N 3 -OPP) by farnesyltransferase . The farnesylated E1-DHFR 2 -CVIA protein (E1-DHFR 2 -N 3 ) was subsequently conjugated with the DBCO-functionalized prodrug DBCO-PEG 4 -VC-PAB-MMAE (DBCO-MMAE) through a strain-promoted click reaction to prepare the desired E1-DHFR 2 -MMAE protein-drug conjugate .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the modularity of this design, fluorinated imaging tags could also be applied to targeting a variety of other extracellular receptors, including those with significantly slower rates of internalization. EpCAM is one such alternative, which we have shown to internalize 24-fold slower than EGFR when targeting with CSANs while maintaining high expression on a variety of solid tumor cells …”
Section: Discussionmentioning
confidence: 99%
“…EpCAM is one such alternative, which we have shown to internalize 24-fold slower than EGFR when targeting with CSANs while maintaining high expression on a variety of solid tumor cells. 38 ■ ASSOCIATED CONTENT * sı Supporting Information…”
Section: ■ Conclusionmentioning
confidence: 99%